2013
DOI: 10.1039/c2dt32312e
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the roles of strictly conserved tryptophan residues in O2producing chlorite dismutases

Abstract: The chlorite dismutases (Clds) degrade ClO2− to O2 and Cl− in perchlorate respiring bacteria, and they serve still poorly defined cellular roles in other diverse microbes. These proteins share 3 highly conserved Trp residues, W155, W156, and W227, on the proximal side of the heme. The Cld from Dechloromonas aromatica (DaCld) has been shown to form protein-based radicals in its reactions with ClO2− and peracetic acid. The roles of the conserved Trp residues in radical generation and in enzymatic function were a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
49
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(53 citation statements)
references
References 38 publications
4
49
0
Order By: Relevance
“…For another functional chlorite dismutase, namely DaCld, the observed ν(Fe-Im) stretching band (222 cm − 1 ) suggests weaker binding between the haeme iron and its proximal ligand compared with NdCld [47]. Even though no direct data concerning the stability of DaCld are available, indirect methods and observations support a lower conformational and thermal stability of DaCld compared with NdCld [24,27,30]. Retrospectively, this correlates with the observed ν(Fe-Im) stretching frequency of both functional Clds.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…For another functional chlorite dismutase, namely DaCld, the observed ν(Fe-Im) stretching band (222 cm − 1 ) suggests weaker binding between the haeme iron and its proximal ligand compared with NdCld [47]. Even though no direct data concerning the stability of DaCld are available, indirect methods and observations support a lower conformational and thermal stability of DaCld compared with NdCld [24,27,30]. Retrospectively, this correlates with the observed ν(Fe-Im) stretching frequency of both functional Clds.…”
Section: Discussionmentioning
confidence: 86%
“…Studies of proximal residue mutants of DaCld and NdCld revealed that manipulation of the rigid H-bonding network in Cld significantly weakens binding of haeme b and thereby destabilizes the protein [25][26][27][28][29][30]. In the present work, we studied the effect of disrupting the proximal H-bonding network by comparing wild-type NdCld with the proximal variants E210A and K141E.…”
Section: Introductionmentioning
confidence: 99%
“…24, 35, 36 The Da Cld crystal structure shows three highly conserved Trp and two Tyr residues within 5 Å of the heme (Scheme 2), any or all of which might in principle provide a conduit for radical migration. 62 The observed reaction of [Fe IV =O] + (AA•) with a single equivalent of ascorbate to yield a ferric species would then most likely be due to selective one-electron reduction of the ferryl iron to the ferric. This might occur if the protein radical species, which one would expect to have proceeded out of the active site, were inaccessible to the reductant.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, a second tryptophan near the heme’s periphery (Trp156) and two residues from a triad of hydrophobic amino acids above the heme plane (Leu185 and Phe200) are strictly conserved among all Clds. The tryptophan appears to be critical for maintaining the bound heme as well as the protein’s oligomeric state [79], and hydrophobicity in the distal pocket may be essential for stabilizing reaction intermediates (see Section 4.2. )…”
Section: Oxygen Generation By Chlorite Dismutasesmentioning
confidence: 99%
“…Indeed, a Compound I species prepared in the stopped flow did not react with exogenously supplied ClO − /HClO to form O 2 , as the reaction appears to be kinetically out-competed by decay of the Compound I intermediate [89]. Though the pathway has not been studied, Compound I’s breakdown has been presumed to occur via the conserved tyrosines that ring (and in one case form hydrogen bonds with) the heme [79]. …”
Section: Oxygen Generation By Chlorite Dismutasesmentioning
confidence: 99%